The review of financial studies. - Society for Financial Studies (New York, N.Y. : Published by Oxford University Press for the Society for Financial Studies, 1988)
A forum for the promotion and dissemination of new research in financial economics.
Place of publication varies: New York, N.Y., 1988-vol. 3, no. 1; Cary, N.C., v. 3, no. 2-
Vol. 2, no. 1-v. 6, no. 3 lack season designations.
Also issued in print.
Mode of access: World Wide Web.
Description based on JSTOR World Wide Web homepage; title from title screen (viewed Feb. 12, 1999).
Latest issue consulted: Vol. 10, no. 4 (winter 1997) (surrogate).
Keywords: Finance -- United States -- Periodicals; Finance -- Periodicals; Finance; United States; Finanzwissenschaft; Zeitschrift; Online-Ressource; Banking, Finance & Investing; Periodicals; Electronic journals; Periodicals